Materiales didácticos y su incidencia en el proceso de aprendizaje del idioma inglés para los estudiantes de educación básica media de la unidad educativa réplica Nicolás Infante Díaz, cantón Quevedo, 2017 - Criollo Vinza., Gonzalo Gabriel (2017)
The objective of this research work is to establish the incidence in the didactic materials in the process of learning the English language for students of Basic Basic Education of the Nicolás Infante Díaz Replica Educational Unit, Cantón Quevedo, 2017. Basic and applied research was used, using the inductive, deductive and analytical-synthetic methods, and observation and survey techniques, applied to teachers and students, whose population is 206, a sample of 186 students was established. On the other hand, interview addressed to the 3 teachers and the rector of the institution, to whom the questionnaires were applied; all this with the purpose of elaborating statistical tables and graphs, using office automation tools that allowed the automation of the answers. The respective methods made possible the study and relationship of the variables, to verify the validity of the hypotheses. It was concluded that the didactic materials in the educational field by the teacher in the process of learning the English language; It is considered the main language of communication between very diverse cultures that share few or no traits in common. It is very useful, so that teachers, when teaching their classes, are dynamic, practical, creative and interactive, making learning clear, precise and meaningful, developing their intellectual abilities without difficulty